METHODOLOGY TO VALUATE AND CLASSIFY WEB ACCESSIBILITY EVALUATION TOOLS - López Zambrano, Javier Hernán (2017)
Taking into account that Web accessibility is the art of ensuring that web portals can be visited and used satisfactorily by as many people as possible, it is indispensable to evaluate the Web contents using the appropriate tools, for this reason, this research work aims to present a methodological model to evaluate these automatic tools, and to select between the existing ones, the highest number of criteria (referred to in WCAG 2.0) can be assessed. The proposed model comprises a cyclic methodology and is called IPAC by the acronym in English of its 4 stages (inspect-plan-assess-categorize), the same ones that are intended to categorize and/or recategorize the Web Accessibility assessment tools, whose built-in functions are changed over time. The validation made in July 2017 of this model resulted in the categorization of the 5 best free license tools for each conformance level (A, AA and AAA).